2021
DOI: 10.1590/1677-5449.200101
|View full text |Cite
|
Sign up to set email alerts
|

Aneurisma de artéria pancreatoduodenal inferior: tratamento endovascular

Abstract: Resumo Os aneurismas das artérias pancreatoduodenais constituem uma afecção rara. Seu diagnóstico é realizado, na maioria das vezes, em situações de emergência por complicações como a rotura, a qual está associada a altas taxas de mortalidade (21-26%). A embolização do saco aneurismático é o tratamento de escolha, devido à sua alta efetividade e menor mortalidade. Neste artigo, é apresentado e discutido um caso de aneurisma de artéria pancreatoduodenal inferior com diagnóstico obtido durante investigação de si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Entre eles, os aneurismas da artéria pancreatoduodenal (AAPD) são os menos frequentes, correspondendo a apenas 2% de todos os AAV. 5 A forma de tratamento preferencial para esse agravo é a terapêutica endovascular.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Entre eles, os aneurismas da artéria pancreatoduodenal (AAPD) são os menos frequentes, correspondendo a apenas 2% de todos os AAV. 5 A forma de tratamento preferencial para esse agravo é a terapêutica endovascular.…”
Section: Resultsunclassified
“…Entretanto, em algumas situações, como suspeita de isquemia visceral, pacientes com anatomia hostil ou quando houve falha do tratamento endovascular prévio, a abordagem aberta é indicada. 5 3.4 ANEURISMA DE ARTÉRIA HEPÁTICA Em 1903 foi descrito pela primeira vez na literatura os aneurismas de artéria hepática (AAH). Entre as etiologias conhecidas, destacam-se aterosclerose, trauma abdominal, procedimentos cirúrgicos, doenças degenerativas, infecções, doença vascular do colágeno e anomalias congênitas.…”
Section: Resultsunclassified
“…PDAA accounts for only 2% of visceral artery aneurysms but has a high mortality rate [ 1 ]. Previous studies have reported that the mortality rate of ruptured PDAA is 21–26% [ 10 , 11 ]. Therefore, PDAA should be treated adequately in the early stages; however, diagnosis is often difficult because it is asymptomatic before rupture and is diagnosed incidentally [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data show that endovascular techniques can be used as the first choice for treating ruptured visceral aneurysms, whether in elective surgery or emergency treatment. [5,13,14] Barrionuevo et al [15] found no statistically significant difference in mortality between open surgery and endovascular therapy through systematic review and meta-analysis. Surgeons are more likely to use intravascular therapy because of shorter hospital stays and a lower rate of cardiovascular complications, but there is a higher rate of reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] Endovascular or interventional treatment is recommended at the time of diagnosis. [4,5] Although the early diagnosis of the disease is essential, PDAA rupture is difficult to distinguish from other abdominal disorders.…”
Section: Introductionmentioning
confidence: 99%